PREVALENCE OF HYPERTENSION AND DIABETES MELLITUS AMONG GROUP C AND GROUP D STAFFS IN A RURAL MEDICAL COLLEGE AND HOSPITAL, INDIA - HALDER, SUJASH; BISWAS, RAJAT KANTI; NASKAR, SUBHRAJYOTI (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: Our aim of this study is to assess prevalence of hypertension and diabetes among Group C and Group D staffs in a Rural Medical College and Hospital of West Bengal, India as well as to assess whether there is difference of these parameters among two groups. Methods: After getting clearance from the Institutional Ethics Committee, this cross-sectional observational unicentric study was done with 44 Group C Staffs and 80 Group D staffs. Results: The study showed that the prevalence of hypertension among the staffs was 8.87% and the prevalence of diabetes mellitus among the staffs was 6.45%. The difference of mean blood sugar among two groups of staffs was not significant, but the difference of mean blood pressure was significant among two groups. Conclusion: As the study involved the health status of important staffs of medical teaching institutes, it will help to implement healthy lifestyle to avoid development of hypertension and diabetes in future among different categories of staffs.